Prospektif Identifikasi Kejadian Medication Error pada Tahap Dispensing High Alert Medication di Instalasi Gawat Darurat (IGD) RSUP Fatmawati Periode November 2025 - Sekar Ayu Rabbani (Jurnal Farmasi Klinik Best Practice, 2025)
Medication errors involving high-alert medications in the emergency department (ED) have the potential to cause serious harm, making early identification during the dispensing stage essential. This study aims to describe potential medication errors related to the storage, distribution, and use of high-alert medications in the ED Pharmacy Depot and emergency trolleys at Fatmawati Central General Hospital. A prospective observational study was conducted in November 2025 through direct observation of the dispensing process, evaluation of emergency trolleys, and interviews with nurses who administer high-alert medications. Incidents were classified using an adapted NCC MERP Index. Seven discrepancies were identified, all of which involved the absence of “high-alert” labels on medication packaging and shelving, as well as limited sticker availability; these discrepancies were categorized as level 1 (potential error without harm). Nurses demonstrated good knowledge of high-alert medications, but were not sufficiently attentive to missing labels. These findings highlight the need for standardized labeling, adequate sticker supply, and routine audits to strengthen patient safety in the ED.